Ain't no makin' it : aspirations & attainment in a low-income neighborhood - MacLeod, Jay (Westview Press, 2009)
Author Jay MacLeod 's classic ethnography--a defining work on the cycle of social reproduction and inequality as lived through the young men from the Clarendon Heights housing project--now includes a third section that continues the lives of the original Brothers and Hallway Hangers through new interviews and analysis.